Oxygen transport to tissue XXXII - LaManna, Joseph C.; Puchowicz, Michelle A.; Xu, Kui; Harrison, David K.; Bruley, Duane F. (Advances in Experimental Medicine and Biology, 2011)
Based on the 2009 proceedings of the 37th annual ISOTT conference, this volume covers all aspects of oxygen delivery to tissue, everything from near infrared spectroscopy, tumor biology, angiogenesis and mitochondrial metabolism to systems modeling, gas transport, hypoxic adaptation and exercise physiology. Special emphasis is placed on methods of oxygen measurement in living tissue and application of these technologies to understanding physiological and biological bases for pathology related to tissue oxygenation. This multidisciplinary volume includes contributions from scientists, engineers, clinicians and mathematicians and is aimed and students and experts from a range of research fields.